The beautiful ‘ugliness’ of gay love : affirmation, recognition, and acceptance of homosexual love through beauty embodied in gay bodies and art. - Tan, Fabian Zhi Yi. (2013)
A young gay man starting out in life and searching for love in a society that persecutes homosexuality finds himself in a quandary, torn between his desire to experience love and quashing it in order to be socially accepted. This situation resonates in the lives of Nicholas Guest and Dorian Gray, the protagonists in Alan Hollinghurst’s The Line of Beauty and Oscar Wilde’s The Picture of Dorian Gray respectively, and remains the dominant focus throughout the novels. The conflict within both protagonists, and the search for a viable way to reconcile the apparent incongruity between their sexual identities and social codes, are encapsulated in Nick’s thoughts as he listens to his boyfriend play the Andante movement of Mozart’s K533 on the piano: “To apologize for what you most wanted to do, to concede that it was obnoxious, boring, ‘vulgar and unsafe’ – that was the worst thing. And the music seemed to know this, to know the irresistible curve of hope, and its hollow inversion” (Hollinghurst 174). Music occupies a middle ground, capturing both the hope for affirmation and acceptance of homosexual love as well as its inverse, when social norms prevents homosexuals from expressing their identities and desires, leading to feelings of emptiness. Music – and art in a broader sense - understands this internal conflict and is able to express what would otherwise be considered ‘vulgar and unsafe’ to a wider audience, albeit subtly and indirectly. More importantly, what the two protagonists, as well as the other gay characters in the novels, seek in and through art is beauty, “the search for beauty being the real secret of life” (Wilde 59). The beauty that the gay characters fervently pursue is embodied in their lovers as well as in art. The former manifests in the bodies of lovers that through a romantic and/or sexual relationship affirm and materialise gay identities, while the latter serves to unveil homosexual love under the veil of ambivalent and polysemic aesthetics in order to gain recognition and acceptance in society. There are however limitations in their pursuits, which in turn determine their ability to actualise social recognition and acceptance.